PERLINDUNGAN ANAK DALAM KONFLIK BERSENJATA INTERNASIONAL ISRAEL–LIBANON 2006: ANALISIS HUKUM HUMANITER INTERNASIONAL - Maria Elsa Karina (Journal of Innovation Research and Knowledge, 2026)
The 2006 international armed conflict between Israel and Lebanon generated severe humanitarian consequences, particularly for vulnerable groups such as children. This article examines the regulation and implementation of international agreements as sources of international humanitarian law governing the protection of children in international armed conflicts, using the 2006 Israel–Lebanon conflict as a case study. This study adopts a normative juridical research method, employing treaty-based, statutory, and conceptual approaches through an analysis of the 1949 Geneva Conventions, the 1977 Additional Protocols, the 1989 Convention on the Rights of the Child, and other relevant international legal instruments. The findings reveal that despite the existence of a comprehensive international humanitarian law framework on child protection, its implementation during the 2006 conflict remained inadequate, as evidenced by persistent and serious violations. This study contributes to the field of international relations by strengthening the discourse on the effectiveness of international humanitarian law in protecting children within the context of contemporary armed conflicts.